Anti-CV2 Autoimmune Encephalitis With Parkinson-Like Symptoms and Bilateral Leukoencephalopathy—A Case Report - Wu, Xuan; Wang, Huayan; Xu, Guorong; Lin, Yu (Frontiers in Neurology, 2019)
Objective: To present a patient with anti-CV2 autoimmune encephalitis admitted for Parkinson-like symptoms and bilateral leukoencephalopathy. Case report: The patient was admitted for Parkinson-like symptoms combined with loss of taste. Serum anti-CV2 antibody was positive. Cranial magnetic resonance imaging revealed bilateral leukoencephalopathy. Breast cancer was detected by positron emission tomography (PET) and ultrasound. Immunotherapy was not performed. Modified radical mastectomy revealed a pT1cN0M0 breast cancer, positive for estrogen and progesterone receptors, and HER2 negative. The resting tremors disappeared by 1 week after surgery. The modified Rankin score (mRS) was 4 before surgery, and decreased to 1 at 9 months after surgery. Conclusion: Anti-CV2 autoimmune encephalitis can present as Parkinsonism with bilateral leukoencephalopathy on MRI. PET scanning can be useful to reveal an occult cancer. Treatment of the cancer may improve the paraneoplastic neurological syndrome without the need of immunosuppressive therapy.